Virtual Reality and Tourism: Visiting Machu Picchu - Diestro Mandos, Jean (2020)
In COVID-19 times, the mobilization of people has become a latent danger due to the possible contagion, consequently people are deprived of visiting archaeological sites in person. Thus, virtual reality emerges as an alternative solution. Individuals can immerse themselves within virtual environments to explore monuments, museums, and other cultural heritage sites. The purpose of this article is to present a system to make virtual visits to the Citadel of Machu Picchu. The UP4VED methodology was used the system construction. The tests of the 3D model were carried out with hotel guests, who showed their satisfaction with the immersive virtual visit to the citadel, considering it an easy-to-use technology that facilitates interaction.